The Rosie effect [large type] - Simsion, Graeme C. (Center Point Large Print, 2015)
The Wife Project is complete, and Don and Rosie are happily married and living in New York and-- surprise-- Rosie is pregnant. Don sets about learning the protocols of becoming a father. Fortunately his best friend Gene is on hand to offer advice: he's left Claudia and moved in with Don and Rosie. As Don tries to schedule time for pregnancy research, getting Gene and Claudia to reconcile, and helping Dave the Baseball Fan save his business, he almost misses the biggest problem of all: he might lose Rosie when she needs him the most.